AN INVESTIGATION INTO THE CONTENT VALIDITY OF A VIETNAMESE STANDARDIZED TEST OF ENGLISH PROFICIENCY (VSTEP.3-5) READING TEST - Thao, Nguyen Thi Phuong (VNU Journal of Foreign Studies, 2018)
This paper investigated the content validity of a Vietnamese Standardized Test of English Proficiency (VSTEP.3-5) Reading test via both qualitative and quantitative methods. The aim of the study is to evaluate the relevance and the coverage of the content in this test compared with the description in the test specification and the actual performance of examinees. With the content analysis provided by three testing experts using Bachman and Palmer’s 1996 framework and test score analysis, the study results in a relatively high consistency of the test content with the test design framework and the test takers’ performance. These findings help confirm the content validity of the specific investigated test paper. However, a need for content review is raised from the research as some problems have been revealed from the analysis.